English language and pedagogical competency of prospective English teachers: insights and challenges from teacher education institutes in Odisha, India - Suar, Gagana Bihari; Behera, Rashmi Ranjan; Rout, Ranjan Kumar; Patra, Sabita; Panda, Prachiprava; Sethi, Pujanjali (Frontiers in Education, 2025)
This study examines the English language competency (ELC) and pedagogical competency (PC) of prospective English teachers in teacher education institutes (TEIs) across Odisha, India. Recognizing the importance of good teacher training for effective language teaching, this research employed a mixed-method approach, assessing a sample of 70 trainee-teachers through a standardized knowledge test complemented by qualitative question, addressing challenges faced by them. The results were concerning, with average scores of 42.36% in ELC and 46.36% in PC, highlighting major gaps in both language proficiency and teaching methods. A one-way ANOVA suggested no significant differences in performance among trainees from different TEIs across Odisha, indicating that all TEIs faced similar challenges. Qualitative analysis highlighted major challenges faced by trainee-teachers including overdependence on old-fashioned methods like the grammar translation method (GTM), limited use of information and communication technology (ICT), English language proficiency issues with teachers, and administrative issues. Despite these impediments, the ongoing educational reforms introduced by the National Education Policy 2020 and Odisha Government present promising opportunities for enhancing teacher education. This study emphasizes the urgent need for comprehensive faculty development initiatives, the adoption of innovative pedagogical practices, and increased utilization of ICT tools within teacher preparation programs. The findings are essential for policymakers, educators, and stakeholders aiming to improve the quality of English language instruction and better prepare future educators in Odisha.